An Ecological Assessment of Wetland Habitats Utilized by Migratory Shorebirds at Kapar, Pantai Remis and Kuala Selangor Nature Park, Malaysia - Marol Riak, Khalid (2004)
The objective of this research was to study the ecology of migrant shorebirds with respect to abundance, migration chronology, behaviour, habitat use, and prey availability. Further investigation was also conducted on the quality of habitats in terms of heavy metals and estimation of plastic pellets distribution at the wetland of Kuala Selangor Nature Park (KSNP) and intertidal mudflats of Kapar and Pantai Remis on the west coast of Peninsular Malaysia during the southward and northward migration period of year 2000- 2002. Total shorebird abundance, number of species and diversity index (Ĥ) were significantly higher in the intertidal mudflats (F = 3843, df=2, P<0.01, F = 193.13, df = 2 P<0.01 and F = 59.75, df = 2 P<0.01 respectively) as compared to the KSNP. Arranged in descending order of abundance; Common Redshanks, Mongolian Plovers, Black-tailed Godwits, Eurasian Curlews, Bar-tailed Godwits, Whimbrels, and Grey Plovers were the dominant shorebird. Endangered species like Asian Dowitchers, Little Stints, and Spoonbilled Sandpipers were also encountered. The results of migration chronologies for shorebirds were distinct and peak abundances generally occurred in the second week of October. Migration chronologies of small sized shorebirds were different (year 2000: χ2 = 116.39, P<0.001; year 2001: χ2=112.92 P<0.001). In year 2000, the migration chronology pattern of medium size probers were different (χ2=49.54 P<0.001), whereas, in year 2001, they were of similar pattern (χ2= 7.35 P>0.05). Results of habitat use revealed that most species utilized intertidal mudflats that are characterized by moist mud, wet mud, and shallow water edge (≤4 cm depth). However, Plovers showed a high preference for dry mud and wet mud. Behavioural data (feeding, locomotion, resting, body maintenance and alertness of three shorebird species (Eurasian Curlews, Common Redshanks and Mongolian Plovers) was different (Wilk’s λ= 0.102, P<0.001). Feeding was the most important activity indicating that, migratory shorebirds used the sites to replenish energy and nutrient reserves. Eight taxa of macrobenthic fauna were encountered, viz Platyhelminthes, Annelida, Brachiopoda, Mollusca, Sipunculida, Arthropoda, Echinodermata, and Chordata. Gastropoda was the most diverse taxa with 16 species. Other diverse groups were the Crustacea (15 species), Polychaeta (14 species) and Bivalvia (10 species). The abundance of macrobenthic fauna was highest in Pantai Remis, followed by Kapar and finally the KSNP. Results of heavy metal (Zn, Cu, Cd and Pb) concentrations in the sediment were significantly different (F= 2.96; df, 2; P <0.05) between the study sites. Concentrations were higher at the KSNP with lower concentration in the mudflats of Pantai Remis. The results of the heavy metal concentration of the macrobenthic fauna ranged from 1.38- 29.13 μg g-1 for Cu, 6-99.76 μg g-1 for Zn and 0.56-1.97 for Pb. A fluctuation in Cd concentration in macrobenthic was at a relatively narrow range of 0.57-1.96 as compared to other metals. The results of plastic pellets indicated that the total frequency of occurrence was highly variable between the sites, being highly significant in Kapar (P<0.05).